An update on the global use of risk assessment models and thromboprophylaxis in hospitalized patients with medical illnesses from the World Thrombosis Day steering committee: Systematic review and meta‐analysis. (13th December 2021) - Forgo, Gabor; Micieli, Evy; Ageno, Walter; Castellucci, Lana A.; Cesarman‐Maus, Gabriela; Ddungu, Henry; De Paula, Erich Vinicius; Dumantepe, Mert; Guillermo Esposito, Maria Cecilia; Konstantinides, Stavros V.; Kucher, Nils; McLintock, Claire; et al.
Abstract: Introduction: Venous thromboembolism (VTE) is a leading cause of cardiovascular morbidity and mortality. The majority of VTE events are hospital‐associated. In 2008, the Epidemiologic International Day for the Evaluation of Patients at Risk for Venous Thromboembolism in the Acute Hospital Care Setting (ENDORSE) multinational cross‐sectional study reported that only approximately 40% of medical patients at risk of VTE received adequate thromboprophylaxis. Methods: In our systematic review and meta‐analysis, we aimed at providing updated figures concerning the use of thromboprophylaxis globally. We focused on: (a) the frequency of patients with an indication to thromboprophylaxis according with individual models; (b) the use of adequate thromboprophylaxis; and (c) reported contraindications to thromboprophylaxis. Observational nonrandomized studies or surveys focusing on medically ill patients were considered eligible. Results: After screening, we included 27 studies from 20 countries for a total of 137 288 patients. Overall, 50.5% (95% confidence interval [CI]: 41.9–59.1, I 2 99%) of patients had an indication to thromboprophylaxis: of these, 54.5% (95% CI: 46.2–62.6, I 2 99%) received adequate thromboprophylaxis. The use of adequate thromboprophylaxis was 66.8% in Europe (95% CI: 50.7–81.1, I 2 98%), 44.9% in Africa (95% CI: 31.8–58.4, I 2 96%), 37.6% in Asia (95% CI: 25.7–50.3, I 2 97%), 58.3% in South America (95% CI: 31.1–83.1, I 2 99%), and 68.6% in North America (95% CI: 64.9–72.6, I 2 96%). No major differences in adequate thromboprophylaxis use were found across risk assessment models. Bleeding, thrombocytopenia, and renal/hepatic failure were the most frequently reported contraindications to thromboprophylaxis. Conclusions: The use of anticoagulants for VTE prevention has been proven effective and safe, but thromboprophylaxis prescriptions are still unsatisfactory among hospitalized medically ill patients around the globe with marked geographical differences.